Modelling Unemployment Insurance A Survey - Potestio, Paola (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book examines unemployment insurance policy through a survey, taking stock of the theoretical work in the field of labor economics. It closely follows and assesses developments in the modelling of optimal unemployment insurance (UI) policies, beginning with the initial analytical findings produced in the second half of the 1970s. A main part of the survey is devoted to the two basic strands of analysis about, respectively, the optimal level of UI benefits and the optimal time profile of UI policy. The book has two different objectives. The first is to provide an essential summary of the individual models, with the intention of underscoring how a number of specific messages for the policy-maker can be derived from analytical constructions. It further emphasizes and comments on what the models deliver to UI policy-makers. The second objective is to stress the importance and extension of open questions in the field of the theoretical approach to the unemployment insurance issue. The survey discusses the multiplicity of heterogeneities of the labor world in particular as relevant for UI issues on the one side, and on the other hand, the independence of the two basic choices of UI policy, its meaning and its limits, and the possible forms of complementarity between these choices. The book is a must-read for researchers, students, and policy-makers interested in a better understanding of the field of labor economics in general, as well as unemployment insurance policies in particular.
Chapter 1. Introduction -- Chapter 2. The starting points -- Chapter 3. The optimal level of unemployment insurance -- Chapter 4. The optimal time profile of UI policy -- Chapter 5. Unemployment insurance over the business cycles -- Chapter 6. Some further notes on the role of a UI system -- Chapter 7. Conclusions.
Keywords: Labor economics; Economic policy; Macroeconomics; Labor Economics; Economic Policy; Macroeconomics and Monetary Economics